Vibration Emissions Reduce Boar Sperm Quality via Disrupting Its Metabolism - Shanpeng Wang; Xuejun Zeng; Shenao Liu; S. A. Masudul Hoque; Lingjiang Min; Nengshui Ding; Zhendong Zhu (Biology, 2024)
Artificial insemination (AI) with liquid-preserved semen has recently become common in pig breeding. The semen doses are produced in a centralized manner at the boar stud and then subsequently distributed and transported to sow farms. However, vibration emissions during transportation by logistic vehicles may adversely affect the quality of boar sperm. Therefore, this study aimed to explore the impact of vibration-induced emissions on sperm quality and function under simulated transportation conditions. Each time, ejaculates from all 15 boars were collected and then pooled together to minimize individual variations, and the sample was split using an extender for dilution. Different rotational speeds (0 rpm, 80 rpm, 140 rpm, 200 rpm) were utilized to simulate varying intensities of vibration exposure using an orbital shaker, considering different transportation times (0 h, 3 h, and 6 h). Subsequently, evaluations were conducted regarding sperm motility, plasma membrane integrity, acrosome integrity, mitochondrial function, adenosine triphosphate (ATP) levels, mitochondrial reactive oxygen species (ROS) levels, pH, glycolytic pathway enzyme activities, and capacitation following exposure to vibration emissions. Both vibration time and intensity impact sperm motility, plasma membrane integrity, and acrosomal integrity. Vibration exposure significantly reduced sperm ATP levels, mitochondrial membrane potential, and the levels of mitochondria-encoded proteins (MT-ND1, MT-ND6) (p < 0.05). After vibration emission treatment, the pH value and mitochondrial ROS levels significantly increased (p < 0.05). Inhibition of sperm glycolysis was observed, with reduced activities of hexokinase (HK), pyruvate kinase (PK), and lactate dehydrogenase (LDH), along with decreased lactate levels (p < 0.05). Additionally, sperm tyrosine phosphorylation levels were significantly reduced by vibration emissions compared to the control group (p < 0.05). After the vibration emission treatment, the number of sperm bound to each square millimeter of oviduct explants decreased significantly compared to the control group (p < 0.05). Similarly, compared to the control group, using semen subjected to vibration stress for AI results in significantly reduced pregnancy rates, total born litter size, live-born litter size, and healthy born litter size (p < 0.05).